Reinterpretasi Epistemologi Pendidikan Islam dalam Filsafat Al-Fārābī sebagai Solusi Krisis Makna Kurikulum Kontemporer - Ahmad, Imam (Yayasan Albahriah Jamiah Indonesia, 2025)
The crisis of meaning in contemporary education is characterized by a disconnect between the spiritual and rational dimensions of the learning process, resulting in a degradation of values ​​and a loss of educational orientation as a means of developing complete human beings. This condition is further exacerbated by the dominance of pragmatic and utilitarian paradigms in modern curricula, which tend to overlook the existential needs of students. This article aims to offer an epistemological contribution through an examination of al-Fārābī's educational philosophy, particularly his idea of ​​the synthesis of revelation and reason as the basis of integral knowledge. Using qualitative methods based on library studies, this study analyzes primary texts by al-Fārābī and secondary literature from Islamic educational thinkers to uncover the relevance of his thinking in the context of the current educational crisis. The results of the study indicate that al-Fārābī’s epistemology emphasizes the harmony between revelation and reason as the foundation of complete learning, positions education as a path to happiness (saʻadah), and emphasizes the importance of a curriculum that integrates ethical, metaphysical, and rational dimensions. In addition, according to al-Fārābī, the ideal teacher figure is a philosopher who can transform knowledge into wisdom and establish a primary society (al-Madīnah al-Fāḍilah) based on noble values. The conclusion of this study confirms that al-Fārābī’s educational epistemology provides a relevant theoretical and practical framework for responding to the crisis of meaning in contemporary curriculum through an integral approach that integrates revelation, reason, values, and knowledge.